Influence on the Result by Abrasion on Filter Casings, Tested in the Environment in Finnmark, Norway - Fabio Manna; Michel Mues; Clara Wiebensohn; Maja Dukat; Andreas Fath (Microplastics, 2025)
The purpose of this study is to determine the plastic wear of the cartridge filter casing 01WTKF (Wolftechnik Filtersysteme GmbH & Co. KG, Weil der Stadt, Germany) when exposed to sand, sediment, and ice at temperatures below 0 °C, both in laboratory and field conditions. Furthermore, this study aims to discuss whether previous studies conducted with the model 01WTKF may suffer significant errors due to abrasion. The freshwater samples were collected in Finnmark, Norway. These samples were filtered using a cartridge filtration method and the 01WTKF filter casing, which features lids made of polypropylene (PP) and bottom parts made of styrene–acrylonitrile copolymer (SAN) or PP. The samples were analyzed for microplastic (MP) cross-contamination by comparing the results of the model 01WTKF to those of the stainless-steel-based model 01WTGD. Laboratory and environmental samples were examined using FT-IR spectroscopy. The results indicate that wear occurs for ice, sand, and sediment. Abrasion significantly increased the overall PP concentration in the environmental samples, introducing an error of 858 ± 516 N m−3 MPs to 2453 ± 92 N m−3 MPs. By contrast, no wear was detected for the SAN-based bottom part. For the PP-based lids, only 92 ± 83 N m−3 MPs were identified. Therefore, the use of PP-based bottom parts and lids is not recommended at temperatures below 0 °C. Additionally, studies utilizing the model 01WTKF should be reviewed and re-evaluated to ensure the accuracy of the obtained data.